A helyi-területi tanácsigazgatás továbbfejlesztése - Kara, Pál (Tér és Társadalom, 1987)
Improving the system of councils in Hungary is a part of an overall socio-economic programme which has as its aim the renewal of the socialist society from the end of the 1960s onwards. Within this, one of the tasks on the agenda, besides the gradual elimination of bureaucratic phenomena in state administration, is the reinforcement of communal autonomy to express and assert the plurality of interests better. This process is to rely on a control system based on supervising instead of commands. The paths leading to the realization of this aim are by now visible. They will affect all council institutions (bodies, officers, elected members, the apparatus etc.) as well as the structural issues. The paper intends to give evidence to this statement by providing an overall review and criticism of the state of affairs. It is of crucial importance to improve the quality of the status of the elected members of the council and their activities as well as to develop the system of control among councils of various levels in such a way as to guarantee the genuine autonomy of local councils by assuring the effective primacy of representative- self-governmental bodies. Within this, the expected and desireable direction of development is to eliminate the so-called dual subordination of executive committees and officers which served to strengthen centralization. It should be made certain that council bodies have direct (‘untransmitted’) control over their executive organizations and that decisions in all matters containing a collision of interests lie with the self-governmental body. The establishment of a two-level system of council administration is an organic part of the realization of this aim over which a political decision has already been taken. Its major element is to place all local councils and their organizations into coordination stressing on the necessity or even the requirement of multilateral co-operation. This solution would, at the same time, transform the role and function of the county councils as well, concerning the content, and the ways and means of their control.